African art as a starting point for an art therapy activity - Vassiliadou Yiannaka, María (Pulso. Revista de educación, 2001)
This article reflects on the organisation of art therapy activities and accessibility to cultural life for all citizens, using a visit to an exhibition of African art with a group of patients from a psychiatric hospital as an example.